Evaluating the Effectiveness of the Role Play Method in Improving Students’ Arabic Speaking Skills: A Case in an Islamic Education Management Program - Maryam Nur Annisa; Fatia Rahmanita; Durrotun Nashihah; Nuriatul Maftukhah; Laily Fitriani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study examines the effectiveness of role play as a pedagogical method for enhancing Arabic speaking skills among students of the Islamic Education Management Program at Sekolah Tinggi Agama Islam Ma’had Aly Al-Hikam Malang. Motivated by the need for more interactive and practice-oriented instruction particularly in non-language departments the study adopts a descriptive qualitative approach, drawing on classroom observations and semi-structured interviews with students and instructors. The findings indicate that role play substantially improves students’ fluency, confidence, and contextual awareness when using Arabic in Islamic educational settings. Instructors play a central role by crafting realistic scenarios, guiding enactments, and offering targeted feedback. Despite challenges such as limited resources, initial student hesitation, and inconsistent preparation, the method fosters an engaging and authentic learning atmosphere. Students reported heightened motivation, practical gains, and deeper cultural linguistic understanding. The study concludes that role play is a valuable addition to Arabic language teaching strategies, particularly in preparing students for professional communication in Islamic educational contexts. Future research should explore its long-term impact and refine implementation across diverse institutional environments.